Knowledge, practice and attitude toward anabolic hormones and nutritional supplements among people practicing sports in the MENA region before and during COVID-19 lockdown - Nael Kamel Eltewacy; Soha Nabil; Rahma Sweedy; Roy Rillera Marzo; Roy Rillera Marzo; Nouran Hamza; Nouran Hamza; The EARG Group (Frontiers Media S.A., 2022)
IntroductionDuring the COVID-19 lockdown, people's lifestyles have changed including their habits and physical activities. There has been an increase in anabolic hormones and nutritional supplement use among people who regularly do exercise in the MENA region. This study aims to assess knowledge, practice, and attitude toward the use of anabolic hormones and nutritional supplements among people who regularly exercise in the Middle East and North Africa (MENA) region and to compare their exercise habits and hormones and supplements usage between before and during COVID-19 lockdown.MethodsA self-administrated online Google form survey was carried out between February 2021 and April 2021. Five thousand eight hundred forty-five participants who regularly exercise and aged ≥18 years responded to the questionnaire. The questionnaire was distributed through social media platforms and included five sections: demographic, training characters, knowledge, practice, and attitude.ResultsThe participants mean age was 27.4 ± 8.6 years. Males represented 58.2 % of participants. 75.3% of the study participants had not used either hormones or supplements, and about 19% used supplements only. The mean percent score for knowledge, practice, and attitude were 39.3 ± 30.5, 1.1 ± 9.5, and 21.3 ± 23.8, respectively. Level of knowledge was higher among participants who worked in the medical field or as sports coaches. The practice was higher among male participants. The most commonly used anabolic hormones and nutritional supplements were steroids and proteins with bodybuilding being the most common purpose. Internet was the main source of information and pharmacy was the main source for procuring these substances. There was a significant decrease in proteins, carbohydrates, and sports drinks used during the COVID-19 lockdown compared to before the COVID-19 lockdown, while a statistically significant increase in vitamins used during the COVID-19 lockdown compared to before COVID-19 lockdown.DiscussionIn the MENA region, there has been an increase in the use of anabolic hormones and nutritional supplements. Most of the population has low knowledge of the harmful effect of uncontrolled, uninformed and unmonitored use of these substances Therefore, increasing the awareness level of participants and sports coaches should be a priority to limit the unsupervised use of hormones and supplements.